Inulin fortified maize-based fermented beverage (Rab) affects lipid profile and blood pressure levels in Indian hyperlipidaemic subjects - Shams, Zahara Ali; Wadhawan, Nikita (International Journal of Environment, Agriculture and Biotechnology, 2024)
This study evaluated the effect of inulin-fortified maize-based Rab on the lipid parameters of 30 hyperlipidemic subjects. The subjects consumed 200 ml of modified Rab (5% inulin) for 28 days. Anthropometric measurements, blood pressure, and lipid parameters were assessed at the beginning and end of the intervention. The data showed that the LDL, total cholesterol, and triglyceride levels were significantly reduced (p<0.05), HDL levels also increased significantly at the end of the intervention period (p<0.05). The results showed that the developed product could be used as a safe alternative to improve the lipid parameters in Indian population.